The Relationship of Nurses' Communication with the Level of Patient Satisfaction in the Surgical Treatment Room of Pelamonia Hospital Makassar - Abdullah, Rusli (Hasanuddin Medan, 2022)
Nurse communication is the process of sending or exchanging information and messages from nurses to patients or vice versa, both verbally and non-verbally with the aim of influencing behavior and responding in order to help overcome client problems. Nurse communication can influence the level of client satisfaction with the nursing services provided. The aim of the research was to determine the relationship between nurse communication and patient satisfaction levels in the Surgical Treatment Room at Pelamonia Hospital Makassar. This type of research is non-experimental research with descriptive methods, with a cross sectional approach. The population in this study was the average number of patients who underwent surgery and were treated each month in the Surgical Treatment Room at Pelamonia Hospital Makassar with a total of 127 patients in 2015. The sample studied was 35 people using a non-probability sampling method with a total sampling technique. Data was collected from March 28 to April 28 2016, using a questionnaire. The results showed that of the 35 respondents studied, the majority of respondents said that nurse communication was good, namely 31 people (88.6%), and the majority of respondents said they were satisfied with the services provided by nurses, namely 29 people (82.9%). Based on the research results, it was concluded that there was a significant relationship between nurse communication and patient satisfaction levels, with a value of p = 0.001 < 0.05. It is recommended that hospital institutions be able to create standard operational procedures (SOP) regarding communication during handover/handover, and can provide further training and education to all staff at the hospital so that they can provide excellent service to patients, especially regarding the communication behavior of nurses and patients.